Variation in different parameters of Nadi and pulse in accordance to Prakriti - Rajesh Kumar Mourya; Narendra Shanker Tripathi; Sushil Kumar Dubey (Wolters Kluwer Medknow Publications, 2022)
Introduction: Nadi Pariksha or pulse examination is one of the important tools for the examination of a healthy and in diseased person which has been recognized not only in ancient systems of medicines but also in the contemporary medicine. It has been included under Ashtavidha Rogi Pariksha by Yogaratnakar which itself signifies its importance, as it is ranked 1st. Methods: Moreover, Ayurveda scholars have many aspects of Nadi Pariksha, many of which are still unexplored. Thus, this exploratory study was designed and done with aim to find out any variation in parameters of Nadi and pulse in accordance with Prakriti. 200 healthy volunteers, willing to participate in the study were selected through purposive sampling method and were subjected for the assessment of Prakriti, Nadi, and pulse examination. Results: It was observed that only few parameters do vary statistically in accordance with Prakriti. Secondly, it was also observed that Nadi and Prakriti are showing some correlation. Irregular pulse was observed in persons having Vata Prakriti by using manual method. While regular pulsation was observed in the persons having Pitta and Kapha Prakriti. Mean value of pulse rate observed maximum in Pitta Prakriti and minimum in Kapha Prakriti persons by manual method. Conclusion: Although it was exploratory study, some relation between Nadi, Pulse and Prakriti has been observed but few of them were not found statistically significant. Second, the difference in observation through Nadi Tarangini method and manual method might have occurred due to the small sample size. Therefore, more researches may be conducted with larger sample size. It can be also said that Nadi and Prakriti are independent parameters and they are showing some correlation.